Dissolution Kinetics of R-Glass Fibres: Influence of Water Acidity, Temperature, and Stress Corrosion - Andrey E. Krauklis; Abedin I. Gagani; Kristine Vegere; Ilze Kalnina; Maris Klavins; Andreas T. Echtermeyer (Fibers, 2019)
Glass fibres slowly degrade due to dissolution when exposed to water. Such environmental aging results in the deterioration of the mechanical properties. In structural offshore and marine applications, as well as in the wind energy sector, R-glass fibre composites are continuously exposed to water and humid environments for decades, with a typical design lifetime being around 25 years or more. During this lifetime, these materials are affected by various temperatures, acidity levels, and mechanical loads. A Dissolving Cylinder Zero-Order Kinetic (DCZOK) model was able to explain the long-term dissolution of R-glass fibres, considering the influence of the pH, temperature, and stress corrosion. The effects of these environmental conditions on the dissolution rate constants and activation energies of dissolution were obtained. Experimentally, dissolution was measured using High Resolution Inductively Coupled Plasma Mass Spectrometry (HR-ICP-MS). For stress corrosion, a custom rig was designed and used. The temperature showed an Arrhenius-type influence on the kinetics, increasing the rate of dissolution exponentially with increasing temperature. In comparison with neutral conditions, basic and acidic aqueous environments showed an increase in the dissolution rates, affecting the lifetime of glass fibres negatively. External loads also increased glass dissolution rates due to stress corrosion. The model was able to capture all of these effects.